PERANAN PARTAI POLITIK DALAM DEMOKRASI DI INDONESIA - Muhammad Jafar AW (Jurnal Administrasi Publik, 2015)
The role of political parties is affecting the condition and future of the nation, because through the results of the election will produce a new leadership , electedthrough a general election . Meaning of democratization in the life of the nation is onewith a general election that will send the nation to the leadership and the newgovernment , in the hope , citizen want the new government will provide improvementsin all areas of life . Thus, the policy change of the state and nation , not lose frompolitical parties role’s that fill with people's democratic party with a vision and missionof the Party which varies in accordance with the ideology